The economics of money, banking, and financial markets - Mishkin, Frederic S. (Harlow, England : Pearson, 2022)
"A college economics textbook for general and business students specializing in money, banking, and financial markets"--
Introduction -- Why study money, banking, and financial markets? -- An overview of the financial system -- What Is money -- Financial markets -- The meaning of interest rates -- The behavior of interest rates -- The risk and term structure of interest rates -- The stock market, the theory of rational expectations, and the efficient market hypothesis -- Financial institutions -- An economic analysis of financial structure -- Banking and the management of financial institutions -- Economic analysis of financial regulation -- Banking industry: structure and competition -- Financial crises -- Central banking and the conduct of monetary policy -- Central banks and the federal reserve system -- The money supply process -- Tools of monetary policy -- The conduct of monetary policy: strategy and tactics -- International finance and monetary policy -- The foreign exchange market -- The international financial system -- Monetary theory -- Quantity theory, Inflation, and the demand for money -- The IS curve -- The monetary policy and aggregate demand curves -- Aggregate demand and supply analysis -- Monetary policy theory -- The role of expectations in monetary policy -- Transmission mechanisms of monetary policy.
Includes bibliographical references and index.
ESS
Book Finder International
Keywords: Finance; Money; Banks and banking